2015
DOI: 10.1103/physrevb.92.201304
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence of superparamagnetism and perfect quantization in the quantum anomalous Hall state

Abstract: Topological insulators doped with transition metals have recently been found to host a strong ferromagnetic state with perpendicular to plane anisotropy as well as support a quantum Hall state with edge channel transport, even in the absence of an external magnetic field. It remains unclear however why a robust magnetic state should emerge in materials of relatively low crystalline quality and dilute magnetic doping. Indeed, recent experiments suggest that the ferromagnetism exhibits at least some superparamag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
126
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(135 citation statements)
references
References 21 publications
(33 reference statements)
6
126
0
1
Order By: Relevance
“…2,13,16 Indeed, a number of studies using global magnetization measurements 14,17,18 and magnetic force microscopy 19,20 have observed FM-like response in magnetically doped TI thin films. Surprisingly, however, recent scanning SQUID magnetic imaging 21 and transport studies, 22,23 as well as analysis of Kerr microscopy imaging, 24 have suggested the presence of a superparamagnetic (SPM) state in Cr-doped (Bi, Sb) 2 Te 3 films in which instead of a long-range FM order the magnetism is comprised of single-domain magnetic islands. These islands are of characteristic size of few tens of nanometers and are only weakly coupled to each other.…”
Section: Introductionmentioning
confidence: 99%
“…2,13,16 Indeed, a number of studies using global magnetization measurements 14,17,18 and magnetic force microscopy 19,20 have observed FM-like response in magnetically doped TI thin films. Surprisingly, however, recent scanning SQUID magnetic imaging 21 and transport studies, 22,23 as well as analysis of Kerr microscopy imaging, 24 have suggested the presence of a superparamagnetic (SPM) state in Cr-doped (Bi, Sb) 2 Te 3 films in which instead of a long-range FM order the magnetism is comprised of single-domain magnetic islands. These islands are of characteristic size of few tens of nanometers and are only weakly coupled to each other.…”
Section: Introductionmentioning
confidence: 99%
“…At low temperatures, small variations of the 3d impurity band affecting the d-shell filling and the bandwidth at E F , e.g. localization of the 3d impurity band, may strongly favor the ferromagnetic superexchange, and influence the onset of ferromagnetism and QAHS recently reported in these systems 2,8,9,14 .…”
mentioning
confidence: 99%
“…Therefore it is of great importance to know in detail the electronic structure at the valence band, and in particular to identify the nature of the electronic states near E F in these systems. In this Rapid Communication we exploit the element-specificity of resonant photoemission (resPES), X-ray photoemission The MBE growth has been described elsewhere 9 . Undoped samples were used as reference in the experiments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Beside transport properties, the mechanism behind strong ferromagnetic ground state in QAH insulators is, however still under debate 26 . One of the proposals is the existence of magnetic impurities on the surface of TI thin film which can enhance local density of state in the band gap 27 and as a consequence, the RKKY interaction in these materials 28 is intensified.…”
Section: Introductionmentioning
confidence: 99%